Utility of ICG fluorescence imaging with vessel clamp for ileocecal resection while preserving ileal conduit constructed after previous total cystectomy - Tomoaki Okada; Kenji Kawada; Takashi Kobayashi; Toshiaki Wada; Yoshiharu Sakai (Surgical Case Reports)
Abstract Background Indocyanine green (ICG) is useful for evaluating the intestinal perfusion of anastomosis. Especially for patients with prior surgeries, ICG imaging enables surgeons in visualizing the anatomical field. Here, we reported the positive and negative staining techniques of ICG fluorescence with vessel clamp for determining the optimal resection area of vessels and mesentery. Case presentation An 80-year-old man, who had an ileal conduit constructed after a prior total cystectomy, was diagnosed with ascending colon cancer. Although the tumor-feeding vessel was primarily the ileocecal artery, there was no detailed information about the blood running through the ileal conduit. At first, the ascending colon and the marginal vessels were transected at distal side of the tumor. Next, both, the ileocecal artery and the marginal artery of oral side of the ileal anastomotic site were clamped. Finally, we injected ICG intravenously to assess the blood flow. As a result, the blood flow between the ileal anastomotic site and transected ascending colon was not identified (negative staining). Therefore, we cut the root of the ileocecal artery, and dissected the peripheral mesocolon including the ileal anastomotic site. After the ileo-ascending colon anastomosis, we injected ICG intravenously again. The blood flow to the ileal conduit was preserved (positive staining). Conclusion ICG fluorescence imaging with vessel clamp can clearly visualize the demarcation line between ischemic and non-ischemic intestinal tract. In colorectal surgeries, this technique is useful to assess the anastomotic perfusion and determine optimal dissection area of vessels and mesentery in secondary intestinal surgery.